Prevalence of Intestinal Parasitic Diseases in HIV Patients in Tabriz(Original article) - Saba Ramezanzadeh; Golam Reza Barzegar; Hamid Oveisi Oskouei; Majid Pirestani; Mahmoud Mahami-Oskouei; Farzaneh Jafarian; Ehsan Ahmadpour; Seyed Abdollah Hosseini (Journal of Ardabil University of Medical Sciences, 2023)
Background: Opportunistic pathogens such as Cryptosporidium, Isospora belli, Blastocystis, etc. cause various gastrointestinal and non-digestive diseases in people with HIV. These symptoms are especially severe in people with HIV who have a CD4 count of less than 200. This study aimed to determine the prevalence of parasitic infections in people living with HIV in Tabriz. Methods: This cross-sectional and descriptive study was performed on137 people with HIV referred to Behavioral Disease Counseling Centers in Tabriz, 2019-2021. Then, after receiving written consent, fecal samples were collected and evaluated for the detection of parasitic infections using direct methods, Ziehl-Neelsen and Trichrome Weber stain. Results: A total of 137 stool samples were collected, including 93 males and 44 females. Most of them were in the age range of 20-60 years. The overall frequency of parasitic infections was 57.7% and the highest prevalence was related to Blastocystis 24.1% and Cryptosporidium 14.6%. Conclusion: Due to the relatively high prevalence of parasitic infections, especially Blastocystis and Cryptosporidium in people with HIV in Tabriz, which can endanger the health of these patients, essential interventions, including personal hygiene training to control and prevent infection with these pathogens, seem to be necessary.